Analysis of relevant legal frameworks on child protection in Malaysia and Nigeria - Alkali, A. Umar; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina (The Department of Private Law, Faculty of Law, University of Maiduguri, Maiduguri, Nigeria, 2016)
Malaysia and Nigeria are signatories to the Convention on the Rights of the Child (CRC). The Convention requires that states parties should strive to ensure that they domesticate the provision of the Convention in their legal frameworks. Malaysia introduces the Child Act 2001 for the purpose of protection of the rights of children in Malaysia. The Act 2001 has made provisions for the protection of children and ensuring that children are given the best care and support up to the time they attain adulthood. The Child Act applies side by side with Islamic law thereby making it applicable and enforceable without much problem. In Nigeria, the Child's Right Act 2003 came on board in line with Nigeria's commitment towards ensuring observance of its commitments of domesticating the CRC. Though, the Child's Right Act has commendably provided various degree of protection to children, its conflict with Islamic law has made most states especially in Northern Nigeria where Muslims constitute majority to decline to domesticate the CRC hence, defeating or at least making the goal of domestication of the CRC not achievable. This article intends to analyse these important frameworks and proposes if Nigeria could benefit from the Malaysian approach.